From Campaign Agenda to Government: The Challenges of Democratic Transitions in Pandemic Age - Reyes Chiriboga, Wendy (2023)
The pandemic accelerated changes in campaigns and electoral processes, along with the predominance of the digital system which manifested the need to transform territorial strategies. Carrying the message together with new values and ways of living, in addition to understanding the public to disenchanted voters, became the main challenge in front of the prevailing need for social distancing. Change is present as a priority in the way of doing politics, in the assessment of rulers and, above all, in the way of handling what is public service. This is why it is necessary to pay more attention to the transition processes and to the first 100 days of government administration. A new leadership exercise is urgently needed, one that will show policies, actions and management, one which may solve the main citizens’problems and which may convey the vision of how a country could be transformed.